DISTANCE LEARNING TO BREAK INTO GURU SHISHYA TRADITION: गुरू शिष्य परम्परा में सेंध लगाती दूरस्थ शिक्षा“ - Sharma, Sangeeta (International Journal of Research -GRANTHAALAYAH, 2015)
Nature brings before us a treasure of happiness in its thousands of colors, but this vibrant color of music has left its impact on the human mind and brain, it is beyond imagination. Music singing, playing and dancing are a coordinated form of the three arts. Presenting these three parts separately is to destroy the liveliness of music. Only by coordinated performance of these three organs does the person become self-centered after being cut off from all external conditions. Music is an art that integrates different sounds, through which the performance of emotions bring out interestingness, melody and beauty. Music is also related to tone and emotion. Music is present in every particle of the universe. The music is unlimited, untouched and uninterested. Scholars have considered music as the greatest means of attaining God. It has also proved that there is confusion, deviation in all the paths of the world. A person wanders into it, but music is the only medium that, while free from all thoughts, leads to the path of salvation. प्रकृति अपने हजारों रंगों में हमारे सामने खुशियों का खजाना लाती हैं, किंतु संगीत के इस चटकीले रंग ने मानव मन और मस्तिष्क पर अपना जो असर छोड़ा हैं, वह कल्पना से परे है। संगीत गायन, वादन तथा नृत्य तीनों कलाओं का समन्वय रूप है। इन तीनों अंगों को अलग-अलग प्रस्तुत करना संगीत की सजीवता को नष्ट करना हैं। इन तीनों अंगों के समन्वित प्रदर्शन से ही व्यक्ति समस्त बाह्यय परिस्थितियों से कटकर आत्मकेन्द्रित हो जाता है। संगीत विभिन्न ध्वनियों को समन्वित करने वाली वह कला है, जिसके द्वारा मनोभावों के प्रदर्शन में रोचकता, माधुर्य एवं सुन्दरता आती है। संगीत का संबंध स्वर तथा भावों से भी होता हैं। संगीत सृष्टि के कण-कण में विद्यमान हैं। संगीत असीमित, अछोर व अशेष है। विद्वानों ने संगीत को ईश्वर प्राप्ति का सबसे बड़ा साधन माना है। यह भी साबित कर दिया है कि संसार के सभी रास्तों में उलझाव है, भटकन है। व्यक्ति इनमें उलझ कर भटक जाता है, परंतु संगीत ही एक ऐसा माध्यम है, जो समस्त विचारों से मुक्त रखते हुए, मोक्ष के मार्ग तक पहुँचाता है।